CYP2C19 genotyping and mavacamten: predicting outcomes in normal, intermediate and rapid metabolisers in obstructive hypertrophic cardiomyopathy - Yande Kasolo; Edward Burford; Mohammed Obeidat; Glenda M Beaman; Thomas Monk; Rachel Bastiaenen; William G Newman; Robert M Cooper (European Journal of Clinical Pharmacology, 2026)
Purpose Mavacamten is the first targeted therapy for obstructive hypertrophic cardiomyopathy (oHCM). It is metabolised via cytochrome p450 enzymes, with variations in the CYP2C19 gene having predominant influence on plasma concentrations of mavacamten. We aimed to outline the effect of CYP2C19 metaboliser status on outcomes in patients taking mavacamten. Methods We retrospectively analysed clinical and echocardiographic data in patients with symptomatic oHCM taking mavacamten. CYP2C19 genotyping was undertaken by loop-mediated isothermal amplification (LAMP) on EDTA whole blood (LaCAR MDx, Liege Belgium) followed by Sanger sequencing of the coding exons of CYP2C19 . Logistical regression was used to assess time taken to optimisation. Results Fifty-five patients (59±13 years; 73% male) were included. Genotyping of CYP2C19*2 , CYP2C19*3 , and CYP2C19*17 alleles was conducted. Due to low numbers in the ultrarapid ( n = 1) and poor ( n = 2) groups, statistical analysis was performed in intermediate, normal and rapid metabolisers. Using normal metabolisers as the reference, there was a non-significant trend towards faster optimisation in intermediate metabolisers (odds ratio 0.63 [95% CI: 0.12–3.19]) and rapid metabolisers (OR 0.55 [95% CI: 0.11–2.53]). While reductions in peak resting (40 ± 34.37 mmHg) and Valsalva (64 ± 35.23 mmHg) left ventricular outflow tract gradients were statistically significant across the cohort ( p < 0.0001), there was no interaction between differing CYP2C19 groups and time ( p = 0.69). Conclusion Excluding poor metabolisers, variations in the CYP2C19 gene do not explain different clinical outcomes in patients with oHCM on mavacamten. Beyond genotyping of the targeted variants, CYP2C19 sequencing did not provide any additional clinically relevant information.